Previously undescribed transient trifascicular block: left septal fascicular block associated with left anterior fascicular block and complete right bundle branch block - Nikus, Kjell; Rankinen, Jani; Virtanen, Raine; Birnbaum, Yochai; Perez-Riera, Andres Ricardo (Elsevier BV, 2026)
Exercise-induced complete right bundle branch block (CRBBB) remains a rare finding during a treadmill test. Both exercise-induced CRBBB and left anterior fascicular block (LAFB) have been associated with coronary artery disease, more specifically with stenosis of the left anterior descending coronary artery. Left septal fascicular block (LSFB) has been associated with acute and chronic coronary syndromes. We describe a patient case with severe left main coronary artery disease. In an exercise test, a rare combination of these three ventricular conduction disorders developed. In a second exercise test after coronary bypass surgery, LAFB and typical CRBBB developed without LSFB.